(3aj eHGOF eMGSHI GdJcGdjas - (3GdSjOYHO GdebUhO(B, (3OHjGfs ((3GdGScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2004)
(3jMJhj gPG GdcJGH Ydi eaGgje GdJcGdja hYdGbGJgG HLhGfH GdfTGW ; JbGQjQ GdeMGSHI GdeGdjI heMGSHI GdJcGdja , JWhQ GdfTGW GdGbJUGOj hCgOGa eMGSHI GdJcGdja , eaJgje GdJcGdja hYdGbGJgG HCMLGe GdGfJGL Ch GdfTGW , eaGgje GdJcGdja hYdGbGJgG HhXGAa GdefTCI ,CfXeI eMGSHI GdJcGdja JbGQjQ hbhGFe ChGeQ GdGfJGL CSS GdbjGS , CfXeI GdbjGS GdJcGdja , fXGe JcGja GdGhGeQ , GdQbGHI Ydi GdJcGdja , GLQGAGJ GdQbGHI Ydi JcGdja GdehGO , GLQGAGJ GdQbGHI Ydi JcGdja GdYed , QbGHI GdJcGdja GdUfGYjI ZjQ GdeHGTQ , eONd GdJcdaI Ydi CSGS GdfTGW (B.s
Keywords: (3GdeMGSHIs; (3eMGSHI GdJcGdjas